In-cell production of a genetically-encoded library based on the θ-defensin RTD-1 using a bacterial expression system. Issue 6 (15th March 2018) - Bi, Tao; Li, Yilong; Shekhtman, Alexander; Camarero, Julio A.
Graphical abstract: Abstract: We report the high-yield heterologous expression of bioactive θ-defensin RTD-1 inside Escherichia coli cells by making use of intracellular protein trans -splicing in combination with a high efficient split-intein. RTD-1 is a small backbone-cyclized polypeptide with three disulfide bridges and a natural inhibitor of anthrax lethal factor protease. Recombinant RTD-1 was natively folded and able to inhibit anthrax lethal factor protease. In-cell expression of RTD-1 was very efficient and yielded ≈0.7 mg of folded RTD-1 per gram of wet E. coli cells. This approach was used to generate of a genetically-encoded RTD-1-based peptide library in live E. coli cells. These results clearly demonstrate the possibility of using genetically-encoded RTD-1-based peptide libraries in live E. coli cells, which is a critical first step for developing in-cell screening and directed evolution technologies using the cyclic peptide RTD-1 as a molecular scaffold.